FACTORS AFFECTING THE EARNINGS RESPONSE COEFFICIENT: AN INDONESIAN PERSPECTIVE - Yen Sun, Nuraini Sari , Kartika Dewi (PalArch’s Journal of Archaeology of Egypt / Egyptology, 2020)
Earnings Response Coefficient (ERC) describes how a market reacts to Earnings announcement which can affect the stock prices. Thus, it is important to know what factors are derived from financial statements that may affect market reaction. This study aims to analyze such factors as leverage, systematic risk, growth opportunities, and company size that have relationships with the ERC by using secondary data of property and real estate companies listed on the Indonesia Stock Exchange within the period of 2013 to 2015. The sampling method used is purposive sampling. The research data were processed by using multiple regression with statistical tools of E-Views program. The results show that growth opportunities have a relationship with ERC, while leverage, systematic risk and size do not have.